Efeito dos hormônios progesterona e β-estradiol em modelos de biofilme microcosmos e monoespécie de cândida spp. derivados de candidíase vulvovaginal - Andrade, Ana Raquel Colares de (2023)
Vulvovaginal candidiasis (VVC) is a disease of the lower female reproductive tract caused by Candida spp. and affects up to 75% of women of reproductive age at least once in their lifetime. As a multifactorial disease, several elements affect in this course, factors inherent to the host, such as female sex hormone levels; and assigned to the pathogen, like the expression of virulence factors and the ability to form biofilms. Therefore, the present study aimed to evaluate the effect of progesterone and β-estradiol on biofilms of Candida spp. in microcosm (MiB) and monospecie (MoB) models, cultivated in Vaginal Fluid Simulating Medium (VSFM) and RPMI 1640, as well the effect of progesterone and β-estradiol in susceptibility of planktonic cells and biofilms of C. albicans cultivated in MSFV and RPMI 1640. Thus, eleven samples/specimens from VVC were applied in tests that evaluated MiB, MoB - VFSM and MoB - RPMI, supplemented with steroid hormones (SH) regarding the production of viable cells, biomass and persistent cells. (PC). Analyses were performed by number of colony forming units (UFC/mL) and biomass. Additionally, 25 previously isolated strains of C. albicans from CVV were tested for their susceptibility againts eight antifungal agentes, in VFSM and RPMI 1640 media. The effects of SH on planktonic cells and biofilms susceptibility for four C. albicans isolates against FLC and CLO was evaluated for CFU/mL and quantification of biomass. It was observed that, in BMi, the presence of SH influenced the reduction of CFU/mL, increased the biomass and stimulated the formation of PC. In BMo - MSFV, SH increased the number of CFU/mL, the quantification of biomass and did not influence the PC production. In BMo - RPMI, HE did not influence the production of CFU/mL, but reduced the quantification of biomass and PC production. The cultivation of planktonic cells in MSFV reduced the susceptibility of C. albicans to five of the eight antifungals tested. HE did not influence the susceptibility of planktonic cells of C. albicans against fluconazole and clotrimazole. BMo – MSFV from C. albicans were unresponsive to treatment with FLC and CLO in the number of CFU/mL, but their biomass was reduced by up to 71%. BMo - RPMI of C. albicans reduced the number of CFU/mL and biomass up to 75% and 73%, respectively. In BMo – MSFV, the presence of HE did not reduce the number of CFU/mL, but reduced the quantification of biomass up to 55% more. In BMo – RPMI, HE reduced the CFU/mL up to 20% more and up to 15% more in the biomass quantification. Finally, the data showed that, at concentrations close to the physiological peaks of the menstrual cycle, HE were able to influence the dynamics and development of Candida spp. biofilms, depending on the study model employed and the strain used. In addition, the use of a culture medium that mimics the vaginal environment allowed C. albicans isolates to present reduced sensitivity to the main antifungal agents used for the treatment of VVC. These findings have an impact on knowledge about the microbiological and pathophysiological aspects of VVC and can elucidate, even if initially, characteristics linked to the increase in therapeutic failures and disease relapses.